Предмет: Математика,
автор: OloloshaOloloeva
Преобразуйте уравнение в квадратное.
(5х-1)^2-(5х+1)^2=(4х+1)^2+(4х-1)^2
Ответы
Автор ответа:
0
( 5X - 1)² - ( 5X + 1)² = ( 4X + 1)² + ( 4X - 1 )²
25X² - 10X + 1 - 25X² - 10X -1 = 16X² + 8X + 1 + 16X² - 2X + 1
- 20X = 32X² + 6X + 2
3X² + 26X + 2 = 0
--------------------------
25X² - 10X + 1 - 25X² - 10X -1 = 16X² + 8X + 1 + 16X² - 2X + 1
- 20X = 32X² + 6X + 2
3X² + 26X + 2 = 0
--------------------------
Автор ответа:
0
Спасибо большое)))
Похожие вопросы
Предмет: Қазақ тiлi,
автор: olga200986
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Химия,
автор: Marker007
Предмет: Математика,
автор: smolinaelenka